The Description of Teacher-Students Interaction in English Speaking at the Tenth Grade of SMA Negeri 3 Gunung Sitoli in 2022/2023 - Glorya Terima Niat Hia; Nursayani Maru'ao; Afore Tahir Harefa; Trisman Harefa (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this study was to describe the interactions between teachers and students that occur in learning English in class X MIPA 1 SMA Negeri 3 Gunungsitoli, using an analytical description. The approach used is a qualitative approach with descriptive methods. The research subjects were teachers and students in class X MIPA 1 SMA Negeri 3 Gunungsitoli. The object of research is the interaction of teachers and students in learning English. Data collection techniques used are observation techniques, documentation and question sheets. The results of the study explain that motivation, school environment and learning schedules do not really affect the process of teacher-student interaction in the learning process. Student responses spoke more in Indonesian, to comment or ask questions. The interaction that occurs is a two-way interaction, this is related to speaking skills and the characteristics of the material being taught. The teacher's role in learning is to explain and give questions and then be answered by students. The interactions that occur are related to the characteristics of the material being taught and the skills that must be achieved by students after learning is complete.